2014
DOI: 10.1016/j.jval.2014.03.1446
|View full text |Cite
|
Sign up to set email alerts
|

Health economic evaluation of canagliflozin in the treatment of type 2 diabetes mellitus in Belgium

Abstract: were driven by drug and treatment costs associated with myocardial infarction. The total cost of saxagliptin/metformin XR group over 20 years was lower than SU plus MET treated group (US$ 14,454,257 vs. US$ 14,735,176). Treatment with saxagliptin/ metformin XR resulted in a greater number of quality-adjusted life years (QALYs) and life-years gained (LYG) than the SU combination (10,203 vs. 9,955 and 12,207 vs. 12,190 respectively). Cost-effectiveness results were robust according to sensitivity analysis. ConCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This was also the case for canagliflozin 100 mg, based on economic evaluations in Spain56 and Poland,57 whereas canagliflozin 300 mg produced an ICER of €181356 and 45,008 zł57 compared with sitagliptin, respectively. Results from additional country-specific analyses versus sitagliptin also suggest that canagliflozin is likely to be a cost-effective option adjunct to metformin, in Ireland,58 France,59 Belgium,60 Slovakia,61 and the Czech Republic 62. Moreover, a NICE HTA for canagliflozin concluded that, due to small differences in costs and QALYs between canagliflozin and DPP-4 inhibitors, both canagliflozin 100 and 300 mg were recommended treatment options in patients inadequately controlled with metformin alone 63…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was also the case for canagliflozin 100 mg, based on economic evaluations in Spain56 and Poland,57 whereas canagliflozin 300 mg produced an ICER of €181356 and 45,008 zł57 compared with sitagliptin, respectively. Results from additional country-specific analyses versus sitagliptin also suggest that canagliflozin is likely to be a cost-effective option adjunct to metformin, in Ireland,58 France,59 Belgium,60 Slovakia,61 and the Czech Republic 62. Moreover, a NICE HTA for canagliflozin concluded that, due to small differences in costs and QALYs between canagliflozin and DPP-4 inhibitors, both canagliflozin 100 and 300 mg were recommended treatment options in patients inadequately controlled with metformin alone 63…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from economic evaluations across different health care systems, including Sweden, Norway, Poland, Belgium, Ireland, and the Czech Republic, suggest that canagliflozin as add-on to metformin is cost-effective, compared with sulfonylureas 53,54,57,60,62,64. In a similar manner, dapagliflozin 10 mg was also dominated by canagliflozin in two economic evaluations in the USA and Spain, utilizing the Economic and Health Outcomes Model for type 2 diabetes mellitus (ECHO-T2DM)65 and the IMS Core Diabetes Model66, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation